2009
DOI: 10.1634/stemcells.2008-0456
|View full text |Cite
|
Sign up to set email alerts
|

Superior Osteogenic Capacity for Bone Tissue Engineering of Fetal Compared with Perinatal and Adult Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) from human adult bone marrow (haMSCs) represent a promising source for bone tissue engineering. However, their low frequencies and limited proliferation restrict their clinical utility. Alternative postnatal, perinatal, and fetal sources of MSCs appear to have different osteogenic capacities, but have not been systematically compared with haMSCs. We investigated the proliferative and osteogenic potential of MSCs from human fetal bone marrow (hfMSCs), human umbilical cord (hUCMSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
265
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(291 citation statements)
references
References 66 publications
14
265
2
1
Order By: Relevance
“…Our data might suggest that BM-MSCs have a weaker response overall and in particular for the radioprotection of vascular EC. Affirmative, earlier reports already suggested that BM-MSCs were less effective for MSC therapy compared to other stem cell sources, for example, compared to adipose tissue-derived or fetal MSCs (64,66,86).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 72%
“…Our data might suggest that BM-MSCs have a weaker response overall and in particular for the radioprotection of vascular EC. Affirmative, earlier reports already suggested that BM-MSCs were less effective for MSC therapy compared to other stem cell sources, for example, compared to adipose tissue-derived or fetal MSCs (64,66,86).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 72%
“…Although this needs to be confirmed in future studies, it may be an example of the role that ''community effects'' or cell-cell interactions/ secreted factors have on the maintenance and control of periosteal progenitor cell populations [2,3]. As well as the colony-forming capacity of Stro-1 + cells, they have been linked with enhanced osteogenicity in vitro [16,48] and cementogenesis in teeth [34]. These observations are confirmed here by a decrease in overall culture when Stro-1 + cells were removed from the general cell population.…”
Section: Discussionmentioning
confidence: 97%
“…However, the majority of studies used ECs [19][20][21][22][23] rather than ECFC. In this project, well-characterized UCB-ECFC were cocultured with hfMSC [7] chosen primarily for their ability to undergo a well-defined osteogenic differentiation pathway [7,24,25] and superiority in osteogenic differentiation over adult counterparts [7,25] for bone tissue engineering applications. We unexpectedly found a twofold enhancement in the osteogenic differentiation of hfMSC when cocultured with UCB-ECFC, and showed that this effect was at least in part through paracrine signaling involving secreted members of the TGF-b superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation, Culture, and Characterization of hfMSC and ECFC hfMSC were isolated from bone marrow as previously described [7]. Briefly, single-cell suspensions were prepared by flushing the bone marrow cells from femurs using a 22-gauge needle, passed through a 70 lm cell strainer (BD Biosciences, San Jose, California, http://www.bdbiosciences.com/home.jsp), and plated on 10-cm diameter plates (NUNC, Thermo Scientific, Rochester, NY, www.nuncbrand.com/us/page.aspx?ID=1238) at 10 6 cells per milliliter.…”
Section: Samples Animals and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation